Global migration governance and mixed flows: Implications for development-centred policies - Steffen Angenendt; Anne Koch (Stiftung Wissenschaft und Politik (SWP), 2017)
Refugee movements, international migration and socio-economic development are intimately bound up together. The impacts of global migratory movements depend on their political management: circumstances conducive to development require close and dependable cooperation between the countries involved. But international cooperation on refugee and migration policy - global migration governance - has to date been weak. Important institutional and policy changes are currently under way, with the Sustainable Development Goals (SDGs) adopted by the United Nations in 2015 including at least some universally binding targets and indicators for migration. And in September 2016 the international community decided to prepare two global compacts - one for migration, one for refugees - within the space of two years. Both will have repercussions for the international institutional setup and the division of responsibilities between UN agencies, including the Office of the United Nations High Commissioner for Refugees (UNHCR), the International Organisation for Migration (IOM) and the International Labour Organisation (ILO). Existing supranational consultative forums in the area of migration can also be expected to gain in political significance. What is required from the development perspective is a normative and institutional reordering of global migration policy - a process the German government should promote and contribute to.
Keywords: 320